Section Area Estimation Methods for Determining the Mechanical Properties of Laser Powder Bed Fusion Thin Wall Structures. (September 2022) - Paradise, Paul; Clonts, Shawn; Niverty, Sridhar; Shinde, Mandar; Suder, Austin; Smith, Tyler; Broderick, Thomas; Benedict, Mark; Chawla, Nikhilesh; Bhate, Dhruv
Abstract: A critical aspect of generating mechanical property data is the accurate estimation of the cross-sectional area of the specimen being tested for computing stress. This ordinarily trivial matter assumes greater significance in the context of thin wall structures (defined here as less than 2 mm thick) fabricated using the laser powder bed fusion process commonly used in metal additive manufacturing. This is primarily on account of the significant surface roughness associated with additively manufactured parts as well as due to variations in cross-sectional area across the gauge. In this work, the thin-wall measurement capabilities of four different metrologies are examined – standard micrometer, point micrometer, blue light 3D scanning, and x-ray computed tomography (XCT) scanning. Seven specimens covering a thickness range of 0.3 to 2 mm are measured by each of the metrologies and tested mechanically, with stress-strain curves derived using the different section area estimates from these metrologies. XCT scanning is chosen as the baseline on account of having the highest resolution of the metrologies under study. Deviations from XCT scanning are established, showing that the standard micrometer is a poor method of choice, particularly at low thicknesses, but that point micrometer measurements are within 5% of XCT measurements across all thicknesses. Blue light scanning is also shown to be a reliable measurement method at all but the lowest thickness, and is also used to estimate the coefficient of variation (CV) in section area within each specimen, showing that the CV rises sharply as specimens get thinner. This paper thus demonstrates, for the first time, the validity of using a point-micrometer for section area estimation, while also showing how variations in section area for thin specimens can contribute to initiation of failure at lower strengths, and thus at least in part explain mechanical debits observed with reductions in thickness.